Proliferating coacervate droplets as the missing link between chemistry and biology in the origins of life - Muneyuki Matsuo (Nature Portfolio, 2021)
Coacervate droplets (CDs) are a model for protocells formed by liquid-liquid phase separation (LLPS), but protocell models able to proliferate remain undeveloped. Here, the authors report a proliferating peptide-based CD using synthesised amino acid thioesters as monomers, which could concentrate RNA and lipids, enabling RNA to protect the droplet from dissolution by lipids.